Kinerja Kereta Api Diesel AC Way Umpu Jurusan Tanjung Karang – Kotabumi dan Kharakteristik Penumpang. - Dwi Herianto; I Wayan Diana; Yoga Tryas Pratama (UNIVERSITAS LAMPUNG, 2013)
Railways as a mode of transportation has special characteristics and advantages.Operating ofKRD AC Way Umpu aims to provide good service and convenient for people of Lampng who wantto go to Kotabumi or to Bandar Lampung.In this study describes the characteristics of KRD passengers based on age, job, income, trip pur-pose, the intensity of the journey, the destination station, level of service, fare and load factor.The results showed overall performance of KRD is quite good.Based on the characteristics of thedata analysis, 62.33% of passengers aged adults (21-40 years old).In terms of jobs, dominated bystudent / college students 34%, 23.33% self-employed, civil servants / military / police22.67%.Rp.1.000.000 is the highest income level, - at 36.67%. Mean 31% of school trips and so-cial visits 47.67%.The intensity of the 1 times a week is49% with the highest purpose the last sta-tion Tanjung Karang96.35% and Kotabumi.Flat fee which resulted in a lack of purchasing powerof travelers in stations along the road to Tanjung Karang or KotabumiSo the impact on the de-cline in load factor at some stations.For the average passenger on a normal day is still appropri-ate capacity provided.